Winning or buying hearts and minds? Cash transfers and political attitudes in Pakistan - Yashodhan Ghorpade; Patricia Justino (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
This paper studies how household-level receipts of cash transfers affect political attitudes in Pakistan. The paper exploits the locally exogenous eligibility cut-off of the flagship Benazir Income Support Programme to estimate causal effects. The main results show evidence of improved satisfaction with the government among beneficiaries of the programme. The paper discusses what potential mechanisms may explain this result and finds no evidence of changes in attitudes being associated with improvements in state capacity or better economic and security prospects. Instead, we find that the effect is present only when the programme has been in place in communities for over two years, which coincides with the switch to proxy-means test-based targeting from the earlier modality of nominations by parliamentarians. The main result is therefore driven by better connected and politically important communities that were favoured by incumbent parliamentarians for programme rollout before the introduction of objective targeting criteria.
Keywords: 330; Social protection; political attitudes; cash transfers; Pakistan